Geometry and Structure of a Fault‐Bounded Extensional Basin by Integrating Geophysical Surveys and Seismic Anisotropy Across the 30 October 2016 Mw 6.5 Earthquake Fault (Central Italy): The Pian Grande di Castelluccio Basin. Issue 1 (3rd January 2019) - Villani, F.; Sapia, V.; Baccheschi, P.; Civico, R.; Di Giulio, G.; Vassallo, M.; Marchetti, M.; Pantosti, D.
Abstract: The Pian Grande di Castelluccio (PGC) basin is the main Quaternary depocenter of the Mt. Vettore‐Mt. Bove normal fault system (VBFS), responsible for the 30 October 2016 M w 6.5 Norcia earthquake (central Italy). Coseismic surface faulting through the basin attests the occurrence of active splays of the seismogenic master fault; thus, we explore the subsurface basin structure to infer the long‐term behavior of the VBFS. We integrate electrical resistivity tomography (ERT), time domain electromagnetic soundings (TDEM), and horizontal‐to‐vertical spectral ratios of ambient seismic vibrations (HVSR) along a transect crossing the surface ruptures. The ERT models provide high‐resolution details of three shallow fault zones. One‐dimensional resistivity models from TDEM and HVSR frequency peaks suggest abrupt steps in the top bedrock caused by previously unknown faults and indicate an infill thickness of up to 300 m. We also analyze shear wave splitting of S phases (fast direction φ and delay time δt ) from local earthquakes recorded during our surveys to better constrain the fracture field and the properties of the inferred fault zones. We relate the retrieved pattern of fault‐parallel φ, and the associated larger δt, to the main and secondary faults in the upper crust and to the cracks or shear fabric in the damage zones of the active splays. The PGC basin is due to the interference of an older N30° striking fault system subsequently crosscut by the N150° striking VBFS, which is currently active, seismogenic, and capable of rupturing the surface during M > 6 earthquakes. Key Points: We explore the subsurface of the Pian Grande di Castelluccio basin, across the 30 October 2016 M w 6.5 central Italy earthquake fault Electrical resistivity models, ambient noise, and seismic anisotropy analyses constrain the basin geometry and the faults pattern The complex subsurface setting is caused by two fault systems with different timing of activity that created 300‐m‐deep depocenters